Evidence for additionally increased apoptosis in the peripheral blood mononuclear cells of major depressive patients with a high risk for suicide. Issue 4 (10th April 2018) - Amidfar, Meysam; Kim, Yong‐Ku; Scaini, Giselli; Quevedo, João
Abstract : Several studies have suggested a pathophysiological role of blood cell apoptosis in major depressive disorder (MDD). The aim of this study was to evaluate mRNA expression levels of Bcl‐2, Bax, and Fas in peripheral blood mononuclear cells (PBMCs) of MDD patients with a high risk for suicide relative to those without a high risk for suicide as well as healthy subjects. The mRNA expression of Bcl‐2, Bax, and Fas as well as the Bcl‐2/Bax ratio was examined in the PBMCs of 30 MDD patients with a high risk for suicide, 30 MDD patients without a high risk for suicide, and 30 healthy controls. The mRNA expression of target genes was measured using real‐time quantitative Polymerase Chain Reaction (PCR). FAS mRNA expression was significantly increased, and Bcl‐2 mRNA expression and the Bcl‐2/Bax expression ratio were significantly decreased, in the PBMCs of MDD patients with or without a high risk for suicide attempts compared to healthy controls ( p  < .001). However, Bax mRNA expression was significantly increased only in MDD patients with a high risk for suicide. Moreover, MDD patients with a high risk for suicide had increased Bax and FAS mRNA expression and decreased Bcl‐2 and Bcl‐2/Bax ratio when compared to patients without risk for suicide ( p  < .001). Our findings may support the role of both internal and external apoptotic pathways in the interplay between the immune system and depressive symptoms, especially in patients with a high risk for suicide.